Six years’ experience and trends of serum 25-hydroxy vitamin D concentration and the effect of vitamin D3 consumption on these trends - Horváth, László; Mirani, Sara; Girgis, Michael Magdy Fahmy; Rácz, Szilvia; Bácskay, Ildikó; Bhattoa, Harjit Pal; Tóth, Béla E. (Frontiers in Pharmacology, 2023)
Introduction: Vitamin D (vitD) deficiency may have importance in some diseases, but there is a lack of data in our country to clarify the current situation. Our aim was to examine the basic characteristics of patients’ vitD status, and the ratio of vitD deficiency and its relation to certain diseases, assess seasonality and trends, and reveal the indirect impact of the COVID-19 pandemic on vitD3 supplementation at the patient population level. Methods: Anonymized data on 25(OH)D test results were obtained from the clinical data registry of a tertiary teaching hospital covering the period between 1 January 2015 and 30 June 2021. VitD consumption (pharmacy sale) data were retrieved from the database of the National Health Insurance Fund of Hungary in order to calculate the defined daily dose (DDD)/1,000 inhabitants/day. Descriptive statistics and odds ratios with their 95% confidence intervals were calculated. The two-sample t-test and F-test were used to analyze our patients’ data. Significant differences were considered if p <0.05. Results: Altogether, 45,567 samples were investigated; the mean age was 49 ± 19.1 years and 68.4% of them were female subjects. Overall, 20% of all patients had hypovitaminosis D, and just over 7% of patients had vitD deficiency. Male subjects had higher odds for hypovitaminosis or vitD deficiency (65.4 ± 28.2 nmol/L vs. 68.4 ± 28.4 nmol/L; p <0.0001). The mean 25(OH)D concentration has changed during the year, reaching a peak in September and a minimum in February. Patients with diseases of the circulatory system, genitourinary system, certain conditions originating in the perinatal period, and “sine morbo” (i.e., without a disease; such as those aged over 45 years and female teenagers) had statistically higher odds for lower 25(OH)D concentrations (p <0.00001). VitD consumption showed seasonality, being higher in autumn and winter. A slight increase started in the season of 2017/18, and two huge peaks were detected at the beginning of 2020 and 2021 in association with the COVID-19 waves. Conclusion: Our data are the first to describe data concerning vitD in our region. It reinforces the notion of vitD3 supplementation for some risk groups and also in healthy individuals. To prevent the winter decline, vitD3 supplementation should be started in September. This and the results during the COVID-19 pandemic highlight the importance of health education encouraging vitamin D3 supplementation.